Statistical characterization for subgrain size and misorientation in the nickel microstructure (2018)
This paper presents the methodology applied in order to develop a statistical analysis of the microstructure in nickel machining. The work is divided into two parts: one of them is focused on analyzing the microstructure (subgrain size and misorientation) from the "rake angle" and "cutting speed" the first part focuses on the analysis of the microstructure (subgrain size and misorientation) based on the "rake angle" and "cutting speed"; in the second part the microstructure is evaluated from the "nose tool radius" the second one evaluates the microstructure with the "nose tool radius". The methodology used in the first part is a design of experiments and an adjustment of the regression model from based on a maximum likelihood model. For the second part, an adjustment was made to the data to evaluate the radius from the cut profile plots and a functional regression model was applied. In the second part, the data was adjusted in order to evaluate the radius based on the cut-profile-plots, and a functional regression model was applied.